Peran Agama Serta Implementasi Komunikasi dan Manajemen Konflik dalam Kerusuhan Sosial di Losari Brebes Jawa Tengah - Muchamad Yuliyanto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
horizontal conflict at Losari beginning from young men fight at two border area that going bigger and become social riot and plundering Chinese shops. Religion as prophetic teaching—that trying to develop equality between men—is actually fails to internalize to their community. Communication and conflict resolution primarily played by actor namely religious and community figure that still have authority or power and honored by their community. Good cooperation between Losari Regency government with religious and community figure is one of key success to perform conflict resolution that begin with communication between two community involved that horizontal conflict.